2017
DOI: 10.1093/intqhc/mzx013
|View full text |Cite
|
Sign up to set email alerts
|

Factors constraining patient engagement in implantable medical device discussions and decisions: interviews with physicians

Abstract: ObjectivePatient engagement (PE) is warranted when treatment risks and outcomes are uncertain, as is the case for higher risk medical devices. Previous research found that patients were not engaged in discussions or decisions about implantable medical devices. This study explored physician views about engaging patients in such discussions.DesignQualitative interviews using a basic descriptive approach.SettingCanada.ParticipantsPracticing cardiovascular and orthopaedic physicians.Main outcome measuresLevel, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…63 Organizational benefits include the development of tools and systems that are more aligned with patients' needs and preferences, 9 simpler and more accessible care pathways and management structures, 9 healthcare professional attitudes that are more favourable to notions of PE and patient-centered care, 64 lower number of admissions in some hospitals, 65 a more cost-efficient health service organization, 13 and improved clinical outcomes. 66 Related to the individual/group and organizational benefits are the pitfalls of not engaging patients in health care activities. Gruman and colleagues (2010) reported that the potential consequences of not engaging patients may include a higher prevalence of preventable medical diseases and errors, lower health and well-being of patients, increased health disparities between groups, and the use of limited healthcare resources inefficiently.…”
Section: Findings: Supporting and Opposing Ideas Supporting Idea: Ethmentioning
confidence: 99%
“…63 Organizational benefits include the development of tools and systems that are more aligned with patients' needs and preferences, 9 simpler and more accessible care pathways and management structures, 9 healthcare professional attitudes that are more favourable to notions of PE and patient-centered care, 64 lower number of admissions in some hospitals, 65 a more cost-efficient health service organization, 13 and improved clinical outcomes. 66 Related to the individual/group and organizational benefits are the pitfalls of not engaging patients in health care activities. Gruman and colleagues (2010) reported that the potential consequences of not engaging patients may include a higher prevalence of preventable medical diseases and errors, lower health and well-being of patients, increased health disparities between groups, and the use of limited healthcare resources inefficiently.…”
Section: Findings: Supporting and Opposing Ideas Supporting Idea: Ethmentioning
confidence: 99%
“…This issue is further complicated by the negative attitudes and perceptions of some healthcare professionals that patients lack the knowledge, understanding, and competency to contribute to healthcare activities. 76 Lack of time and resources and negative attitudes towards patients may originate from viewing patients as distinct components of the healthcare system insofar that one group, the conventional healthcare professionals, design and deliver care to another group, the patients, who serve as passive consumers of health services.…”
Section: Professionalization Of Patientsmentioning
confidence: 99%
“…The acknowledgement of patients as important contributors to the health care system has led to the proliferation of primary research on the barriers, facilitators, impacts, and strategies of PE. [19][20][21][22][23][24][25] As such, there is a need to synthesize the evidence base. There are many published reviews of PE, but they are topic-and context-specific.…”
Section: Planning and Designing Of Health Servicesmentioning
confidence: 99%